Larval host plants and metamorphosis of selected butterfly species (Rhopalocera) in La Union Botanical Garden (LUBG), San Fernando, La Union, Philippines - Nacua, Alma E. (Animo Repository, 2015)
Host plants are known to support growth of different butterfly species in the larval stage. Butterfly larvae are characterized by being voracious eaters and host plant specific. However, information regarding larval host plants of many butterfly species remains poor in the Philippines. The paper aimed to provide information on the larval host plants of the butterflies and document some butterfly life cycles in La Union Botanical Garden, San Fernando, La Union (LUBG), Philippines. The study employed visual searching for eggs and larvae in the foliage along the 100-meter line transects established in LUBG. Larval host plants were determined when larvae feed on the plant particularly leaves or flowers. The study on the life cycle or metamorphosis of selected butterfly species utilized field observation and description using ocular micrometer under the microscope. The data revealed 66 species in 27 families of larval host plants that support 57 species in 4 families of butterflies. The results suggest that presence and abundance of larval host plants affect butterfly metamorphosis and abundance in LUBG.